Electoral apathy among Chilean youth: New evidence for the voter registration dilemma (Estudios Gerenciales, 2017)
The decision of voter enrollment among Chilean youth is re-examined in this paper. Geographical and gender differences regarding what determines voter-registration rate among youth are also explored. Electoral and socioeconomic data are collected from 272 Chilean counties in order to estimate the fractional-response and the random-effects Tobit models. The results indicate that the voter registration rate is higher among lower-income youth, which differs from earlier studies, and redefines the implications of a class-biased electorate in Chile. Furthermore, the evidence suggests an increasing political disaffection among indigenous youth that reside in rural counties.